Sensory Neuropathy of the Foot Among Asymptomatic Patients of Type II Diabetes Mellitus - Syed Mazhar Ali shah; Bilal, Muhammad; Saima Khattak; Mian Fereezuddin; Yaseen Khan (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: This Study aimed to determine the frequency of sensory neuropathy in the feet of asymptomatic people with type II diabetes mellitus. METHODOLOGY: This cross-sectional Study was conducted at the medical department of MTI/Lady Reading Hospital, Peshawar, between April - October 2022. A total of 133 patients were observed using a non-probability consecutive sampling technique. Patients aged 25-60 years who had type II diabetes mellitus for more than one year were included, while patients with vitamin B12 deficiency who used multivitamins were excluded from the study. SPSS version 20 was used for statistical analysis. RESULTS: Age-wise distribution 25-30 Years (4.5%), 31-40 Years (21.8%), 41-50 Years (45.9%), and 51-60 Years (27.8%) (mean 45.56±3.3). Gender-wise, 104 (78.2%) were male and 29 (21.8%) were female. Regarding education level, 57 (42.9%) were illiterate, 46 (34.6%) had secondary education, and 30 (22.6%) had higher education. Residency status indicated 105 (78.9%) from urban areas and 28 (21.1%) from rural areas. Socioeconomic status was distributed as follows: 53 (39.8%) with a monthly income >100,000 Rs, 46 (34.6%) with an income range of 50,000 to 100,000 Rs, and 34 (25.6%) with an income range <50,000 Rs. Sensory neuropathy was found in 60 (45.1%) patients and absent in 73 (54.9%). CONCLUSION: The Study revealed a notably high prevalence of sensory neuropathy. Prompt identification and focused treatment are essential, especially for patients over 40, sedentary lifestyles, and those with diabetes for more than two years.